2022
DOI: 10.1007/s10072-022-06156-y
|View full text |Cite
|
Sign up to set email alerts
|

Floating aortic arch thrombus involving the left common carotid artery complicated with ischemic stroke associated with cocaine use

Abstract: Background Floating aortic thrombi (FLOAT) are rare, with very few cases attributed to cocaine use. We report a new case of FLOAT involving the left common carotid artery due to cocaine use, for the first time, complicated with acute ischemic stroke. Methods We present in detail our case report, and then, a literature search in PubMed and Scopus was performed up to March 20, 2022, to review the reported cases of aortic thrombus associated with cocaine use. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…7 Previous reports discuss various cocaine-induced thromboses including deep vein thrombosis and pulmonary embolism, myocardial infarction from intracoronary thrombus despite normal coronary arteries, and floating aortic arch thrombus. [8][9][10] Our case suggests CST may similarly be triggered by cocaine use.…”
Section: Discussionmentioning
confidence: 68%
“…7 Previous reports discuss various cocaine-induced thromboses including deep vein thrombosis and pulmonary embolism, myocardial infarction from intracoronary thrombus despite normal coronary arteries, and floating aortic arch thrombus. [8][9][10] Our case suggests CST may similarly be triggered by cocaine use.…”
Section: Discussionmentioning
confidence: 68%
“…Although these reports have not demonstrated a standardized technique for the mechanical thrombectomy of CFFTs, numerous methods including stentrievers, reversal of carotid flow with occlusion balloons, and distal filter wire placement have been reported. [6][7][8][9][10][11][12][13][14][15][16][17] Recently, direct aspiration, with or without the utilization of proximal and distal protection devices have been described. 11,20,27 To harness all the benefits of previously reported techniques we employed a triple stentriever "bouquet" technique for the mechanical thrombectomy of a CFFT.…”
Section: Discussionmentioning
confidence: 99%
“…5 There have been several recent reports about the successful mechanical thrombectomy of CFFT. [6][7][8][9][10][11][12][13][14][15][16][17] These studies have demonstrated the challenges of safely performing mechanical thrombectomy due to significant clot burden, lack of tools, and techniques designed to perform cerebrovascular thrombectomy. In total, the literature to date has provided no conclusive techniques for safe and reliable removal of CFFTs.…”
mentioning
confidence: 99%
See 1 more Smart Citation